Cartographie de la croissance urbaine de Kinshasa (R.D. Congo) entre 1995 et 2005 par télédétection satellitaire à haute résolution - Matthieu Kayembe Wa Kayembe; Mathieu De Maeyer; Eléonore Wolff (Belgeo)
The urban growth of Kinshasa (DRC) is mapped by classification of built-up areas using SPOT images dating from 1995 and 2005. From the results, the city growth is slower than the population growth; it is taking place within interstitial areas despite their steep slopes and their distance (1 km) from the main communication axes.